Exploring the feasibility and acceptance of an optimised physiotherapy approach for lateral elbow tendinopathy: a qualitative investigation within the OPTimisE trial - Chris Littlewood; Marcus Bateman; Jonathan C Hill; Benjamin Saunders; Karin Cooper (BMJ Open, 2024)
Objectives To explore the acceptability of an optimised physiotherapy (OPTimisE) intervention for people with lateral elbow tendinopathy (LET) and feasibility of comparing it to usual care in a randomised controlled trial.Design Semistructured interviews, analysed using thematic analysis and mapped onto the COM-B model of behaviour change.Setting Conducted as part of the OPTimisE Pilot & Feasibility randomised controlled trial within physiotherapy departments in the United Kingdom National Health Service.Participants 17 patients with LET (purposively sampled to provide representativeness based on age, sex, ethnicity, deprivation index and treatment allocation) and all 8 physiotherapists involved as treating clinicians or site principal investigators.Results Four themes were identified. First, participants reported the OPTimisE intervention as acceptable. Second, differences between the OPTimisE intervention and usual care were identified, including the use of an orthosis, holistic advice/education including modifiable risk factors, forearm stretches, general upper body strengthening and a more prescriptive exercise-dosing regimen. Third, participants provided feedback related to the trial resources, which were viewed positively, but identified language translation as a need. Fourth, feedback related to trial processes identified the need for changes to outcome collection and reduction of administrative burden. From the perspective of adopting the OPTimisE intervention, we found evidence that participants were able to change their behaviour. Considering the findings through the lens of the COM-B model, the intervention is likely to be deliverable in practice and the trial can be delivered at scale with some additional support for physiotherapists.Conclusions Overall, the OPTimisE intervention was found to be different to usual care and acceptable to patients and physiotherapists. The study highlighted the need to refine trial processes and resources prior to a full-scale trial, to reduce administrative burden, increase support for physiotherapists, improve return rate of outcome questionnaires and provide language translation.Trial registration number ISRCTN database 19 July 2021. https://www.isrctn.com/ISRCTN64444585.